Orlando : a biography - Woolf, Virginia, 1882-1941; Ackroyd, Peter; Reynolds, Margaret; Lyons, Brenda (Editor) (London : Vintage book, 2004)
"First masculine, then feminine, Orlando is a young sixteenth-century nobleman who gallops through the centuries, from Elizabethan England and imperial Turkey to Virginia Woolf's own time. Will he find happiness with the exotic Russian princess Sasha? Or is the dashing explorer Shelmerdine the ideal man? And what form will Orlando take on the journey-a nobleman, traveler, writer? Man or . . . woman? Written for the charismatic, bisexual writer Vita Sackville-West, Orlando is one of Woolf's most popular and accessible novels, a playful mock biography of a chameleon-like historical figure that is both a wry commentary on gender and, in Woolf's own words, a "writer's holiday" that delights in its ambiguity and capriciousness. Penguin Vitae-loosely translated as "Penguin of one's life"-is a deluxe hardcover series from Penguin Classics celebrating a dynamic and diverse landscape of classic fiction and nonfiction from seventy-five years of classics publishing. Penguin Vitae provides readers with beautifully designed classics that have shaped the course of their lives, and welcomes new readers to discover these literary gifts of personal inspiration, intellectual engagement, and creative originality"--
First published in Great Britain by The Hogarth Press 1928. Annotated edition published in Penguin Books (UK) 1993. Published with a new foreword in Penguin Books (USA) 2024.
Includes bibliographical references.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Transsexuals -- Fiction; Nobility -- Fiction; Sex role -- Fiction; Aristocracy (Social class) -- Fiction; England -- Fiction; Fiction